Initial exploration of the genetic structure of domestic pig (Sus scrofa domestica) in Sampués, Sucre, Colombia, using microsatellites - Pardo P., Enrique (2017)
The aim of this research was to evaluate the genetic variability of a population of domestic pigs (Sus scrofa domestica) in Sampués, Sucre, Colombia to determine their genetic status. Fifty samples were studied. Twenty microsatellites were used where five of them were from the list of those recommended by FAO/ISAG for studies of swine biodiversity and the remaining represent most of the pig genome. The microsatellites used were polymorphic, detecting between 3 (SW2019) to 14 (SW957) alleles with an average 6 and a total of 120. The mean expected heterozygosity was 0.5465 and the mean observed heterozygosity was 0.5203. The polymorphism information content (PIC) ranged between 0.2823 and 0.7252 for SW1041 and SW957 loci respectively. The results showed that the studied population as a group with a high degree of genetic diversity.